Sensor Less BLDC Motor Drive Using a Multi-Sector Space Vector PWM Method Based on Adaptive Network-Based Fuzzy Inference System - Kumar, Ch. Vinay; Rao, G. Madhusudhana; Ram, A. Raghu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This article describes the process of developing a MS-SVPWM controls BLDC motor rotational speed. This innovative control approach improves BLDC efficiency at a variety of speeds and loads. Construction of the prototype around a brushless DC motor with 400 W of output power, 30 V of voltage, and 3000 rpm of rotational speed. The drive’s unregulated rectifier supplies the necessary DC current to the inverter. The desired drive control is an MS-SVPWM scheme with ANFIS control. By contrasting the operation of conventional space vector PWM& with that of a multi-sector SV-PWM system, ANFIS controllers can choose the best drive sector & detect mismatched pulses. This unique switching control mechanism not only improves the efficiency of the BLDC system but also reduces the switching losses experienced by the inverter. This MS-SVPWM effectively reduces undesired distortions like THD, torque, & DC voltage ripple. To check the feasibility of the proposed system, MATLAB Simulink simulations are run. System simulation and experimental findings for the RP2040-controlled MS-hardware SVPWM are presented.